Monitoring and Mapping of Insecticide Resistance in Vector of Cutaneous Leishmaniasis, Phlebotomus Papatasi (Diptera: Psychodidae) in Iran (Global Journal of Medical Research, 2021)
Sandfly, Phlebotomus papatasi is an important vector of zoonotic cutaneous leishmaniasis (ZCL) that plays the main role in the transmission of leishmaniasis in Iran. ZCL is one of the most common endemic diseases in Iran. The prevalence of resistance to insecticides in vector species around worldwide is a serious threat to the fight against vector-borne diseases. To provide authentic information about this novel, the reliable data on academic resources such as Google Scholar, Scopus, Web of Science, Springer, Pro-Quest, Wiley Online, Science Direct, Research Gate, PubMed, Sage, and SID were used. There are some levels of resistance in some parts of Iran like, Lorestan and Isfahan province. Resistance to DDT 4% was observed in some parts of Iran. In Lorestan province -Pol-e Dokh-tar, Rumeshgan, and Kuhdasht districts-samples collected in the form of hand catch and indoors showed resistance to DDT 4%.Studies in the rural district of Badrood, Natanz County, Esfahan province showed resistance to DDT 4%.
Keywords: phlebotomus papatasi; insecticide; resistance; leishmaniasis; Iran